A business plan for the startup of Mojo Dojo Martial arts studio - Chew, Eldric Hui Jun (2023)
This business proposal has been created to seek new investors that will help to build and work alongside the CEO in the creation of Mojo Dojo. Mojo Dojo will be a Self-training martial art studio with 24-hour access, equipped with state-of-the art martial art training technology where virtual trainers are able to assist users. At the same time, skilled users can train at their own pace instead of having to join fixed classes organised by existing studios. The business will be selling monthly membership or pay-per-use access to the facilities with no tie down periods.